Rattus leucopus Gray 1867 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus leucopus Gray 1867 Rattus leucopus Gray 1867, Proc. Zool. Soc. Lond., 1867: 598. Type Locality: Australia, Queensland, Cape York (as restricted by Thomas’ lectotype selection; see Mahoney and Richardson, 1988:183). Vernacular Names: Cape York Rat. Synonyms: Rattus cooktownensis Tate 1951; Rattus dobodurae Troughton 1946; Rattus mcilwraithi Tate 1951; Rattus personata (Krefft 1867); Rattus ratticolor (Jentink 1908); Rattus ringens (Peters and Doria 1881); Rattus terra-reginae (Alston 1879). Distribution: Australia, Queensland: one population ranges from the tip of Cape York south down E side of the peninsula to vicinity of Coen, another from region of Cooktown south along the coast to Tully; all records are east of the Great Dividing Range (Moore and Leung, 1995; Taylor and Horner, 1973; Watts and Aslin, 1981). New Guinea: widespread in lowlands south of Central Cordillera, in N and S lowland regions fringing the Owen Stanley Range in E Papua New Guinea (Flannery, 1995 a Taylor et al., 1982:232); also Wokam Isl in the Aru Isls (Flannery, 1995 b ). Altitudinal range, sea level to 1200 m (Flannery, 1995 a ). Conservation: IUCN – Lower Risk (lc). Discussion: Rattus leucopus species group. This species and R. sordidus are the only two native Rattus occurring on both New Guinea and the NE coastal region of Australia (Taylor et al., 1982). Morphologically related to other species of Rattus native to New Guinea (Taylor et al., 1982). Morphological data interpreted by Taylor and Horner (1973) to indicate close affiliation between R. leucopus and R. fuscipes from coastal Queensland; allozymic data discordant with this view (Baverstock et al., 1983 a , 1986). Australian segment reviewed by Watts and Aslin (1981), Mahoney and Richardson (1988), and Moore and Leung (1995); New Guinea segment reviewed by Flannery (1995 a ). Leung (1999 b ) provided the first detailed ecological study of R. leucopus in Australia. Leary and Seri (1997) discussed specimens taken in the Kikori River Basin of S Papua. Published as part ...